Efficiency in the process industry: Three thermodynamic tools for better resource use. (October 2020) - Kjelstrup, Signe; Magnanelli, Elisa
Abstract: In a world where resources are limited and their use will necessary have an impact, efficient handling of resources becomes essential. This review concerns three thermodynamic tools that can be systematically used to evaluate and improve resource use. The tools are related to the second law of thermodynamics, which sets a general framework for all conversion processes, including food processing. We address the benefits of using exergy analysis to map the losses of energy quality in a process. This can be done at every scale, from a nation scale to a process unit, and the results of the analysis can be used at different levels of decision making processes, by policy makers, plant managers, scientists or engineers. Moreover, knowledge on coupling between transport processes can be used to drive processes using driving forces other than the conventional ones. This would allow us to recover some of the resource potential which is currently wasted (e.g. process waste heat). Finally, inspiration for efficient design can be found in nature; two examples of nature-inspired chemical engineering (NICE) design are reviewed and used to encourage a development in this direction. Highlights: We explain why the second law of thermodynamics is central for evaluation of efficient resource use. We explain why exergy analysis gives a useful overview of losses. We propose that thermal driving forces are better exploited. We suggest that inspiration can be found in Nature, to include structure as a variable when we are seeking the optimal design. Graphical abstract: